Rotavirus Stimulates Secretion of Interleukin-1beta (IL-1β) in Children with Gastroenteritis - H. Al-Saffar, Venus (International Journal of Psychosocial Rehabilitation, 2020)
Forty patients were diagnosed with rotavirus in children with acute diarrhea using the agglutination test. ELISA was used to compare the immunologic evaluation of the IL-1β in 40 kids with severe diarrhea and 40 in the healthy group. The results indicated that there was no significant difference between those with diarrhea and the control group.